The unlocked leader dare to free your own voice, lead with empathy, and shine your light in the world - Gentil, Hortense le; Lambert, Caroline (John Wiley & Sons, Inc., 2024)
"For decades, the traditional view was that to be successful, business leaders must be superheros? infallible, unflappable, in control, and fearless? or at least pretend to be. As a global executive coach, I work with many superhero-leaders. These smart and successful executives are masters at leading with their head. Yet they don't know how to lead with their heart and their soul, too. In today's unpredictable and fast-changing business environment, no single person has all the answers. The best leaders are strong *and* vulnerable? they show their human weaknesses as a way to connect with people, create a safe and supportive environment, and mobilize them around an inspiring vision. If this sounds like la-la land, consider this. First, the world has changed. Second, employees have changed, too. Over half are struggling, feeling overworked, disconnected, unheard and suffering from digital burnout. To give the best of themselves, they need leaders who are human, too, unafraid of showing empathy and vulnerability: not distant semi-gods with whom there can be no genuine connection. The leader's journey involves three steps: first identifying the mind trap that stands in the way, then operating a mind-shift to defuse it, and finally engineering a mind-build to anchor a new perspective"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on October 10, 2023)
Keywords: Leadership -- Psychological aspects; Personnel management -- Psychological aspects; Strategic planning; Leadership; Aspect psychologique; Personnel; Direction; Aspect psychologique; Planification stratégique; Leadership; Psychological aspects; Personnel management; Psychological aspects